siRNA Specificity: RNAi Mechanisms and Strategies to Reduce Off-Target Effects - Neumeier, Julia; Meister, Gunter (Frontiers in Plant Science, 2021)
Short interfering RNAs (siRNAs) are processed from long double stranded RNA (dsRNA) and a guide strand is selected and incorporated into the RNA-induced silencing complex (RISC). Within RISC, a member of the Argonaute protein family directly binds the guide strand and the siRNA guides RISC to fully complementary sites on-target RNAs, which are then sequence-specifically cleaved by the Argonaute protein - a process commonly referred to as RNA interference or RNAi. In animals, endogenous microRNAs (miRNAs) function similarly but do not lead to direct cleavage of the target RNA but to translational inhibition followed by exonucleolytic decay. This is due to only partial complementarity between the miRNA and the target RNA. SiRNAs, however, can function as miRNAs and partial complementarity can lead to miRNA-like off-target effects in RNAi applications. Since siRNAs are widely used for screening but also therapeutics and also crop protection purposes, such miRNA-like off-target effects need to be minimized. Strategies such as RNA modifications or pooling of siRNAs have been developed and are used to reduce off-target effects.